Global motion perception is associated with motor function in 2-year-old children. (29th September 2017) - Thompson, Benjamin; McKinlay, Christopher J.D.; Chakraborty, Arijit; Anstice, Nicola S.; Jacobs, Robert J.; Paudel, Nabin; Yu, Tzu-Ying; Ansell, Judith M.; Wouldes, Trecia A.; Harding, Jane E.; ,
Highlights: Global motion perception is associated gross motor function at 2 years of age. Stereopsis is associated with fine motor function at 2 years of age. Acuity is not associated with motor function at 2 years of age. Visual and motor dorsal stream sub-components are associated early in development. Abstract: The dorsal visual processing stream that includes V1, motion sensitive area V5 and the posterior parietal lobe, supports visually guided motor function. Two recent studies have reported associations between global motion perception, a behavioural measure of processing in V5, and motor function in pre-school and school aged children. This indicates a relationship between visual and motor development and also supports the use of global motion perception to assess overall dorsal stream function in studies of human neurodevelopment. We investigated whether associations between vision and motor function were present at 2 years of age, a substantially earlier stage of development. The Bayley III test of Infant and Toddler Development and measures of vision including visual acuity (Cardiff Acuity Cards), stereopsis (Lang stereotest) and global motion perception were attempted in 404 2-year-old children (±4 weeks). Global motion perception (quantified as a motion coherence threshold) was assessed by observing optokinetic nystagmus in response to random dot kinematograms of varying coherence. Linear regression revealed that global motion perception was modestly, but statistically significantly associated with Bayley III composite motor (r 2  = 0.06, P < 0.001, n = 375) and gross motor scores (r 2  = 0.06, p < 0.001, n = 375). The associations remained significant when language score was included in the regression model. In addition, when language score was included in the model, stereopsis was significantly associated with composite motor and fine motor scores, but unaided visual acuity was not statistically significantly associated with any of the motor scores. These results demonstrate that global motion perception and binocular vision are associated with motor function at an early stage of development. Global motion perception can be used as a partial measure of dorsal stream function from early childhood.